Study on mechanical, wear, corrosion and fracture characteristics of Al7075 by modifying nano sized Magnesium (n-Mg) element (Fracture and Structural Integrity, 2025)
Aluminum alloys are widely used in the automobile industry because of their excellent mechanical strength, low weight, and remarkable resistance to corrosion and wear. The purpose of this study is to investigate how the microstructure, mechanical properties, and corrosion resistance of the Al7075 alloy are affected by the addition of nano sized magnesium (n-Mg) particulates. Stir casting was used to fabricate the alloy samples, which had varied wt. % of n-Mg (0, 1, 1.5, 2, and 2.5 wt. %). By studying corrosion, wear, microstructural, and mechanical characteristics, the impact of n-Mg dispersion was assessed. The findings provided crucial information on magnesium's function in fortifying aluminum by demonstrating that optical micrographs depicted a homogeneous distribution of n-Mg particles within the Al7075 matrix. Magnesium at the nanoscale improved the alloy's strength, reduced dislocation motion, and refined the grain structure. However, as evidenced by a decrease in impact energy, the addition of magnesium also resulted in decreased toughness and ductility. Tensile strength, hardness, wear resistance, as well as corrosion resistance all improved by roughly 9.21%, 15.73%, 18.82%, and 23.80%, respectively, in the modified Al7075 alloy.
Keywords: Al7075; n-Mg; Stircasting; Microstructure; Hardness; Tensile; Wear; Corrosion behavior; Fracture surface